'Gender discrimination is stopping women pursuing leadership roles in our profession'. (23rd April 2021) - Moore, Alice
Abstract: Alice Moore argues that gender discrimination is still a big problem in the veterinary profession and that the tendency to focus purely on the gender pay gap is not helpful in solving the wider issues.